Exploring the Chemical Composition and Antimicrobial Activity of Extracts from the Roots and Aboveground Parts of Limonium gmelini - Dariya Kassymova; Francesco Cairone; Donatella Ambroselli; Rosa Lanzetta; Bruno Casciaro; Aizhan Zhussupova; Deborah Quaglio; Angela Casillo; Galiya E. Zhusupova; Maria Michela Corsaro; Bruno Botta; Silvia Cammarone; et al. (Molecules)
Limonium gmelini (Willd.) Kuntze, a plant widely used in traditional medicine, has garnered increasing attention for its diverse pharmacological activities, including anti-inflammatory, hepatoprotective, antioxidant, and antimicrobial effects. This study aimed to explore the chemical composition and biological activities of polysaccharides and polyphenolic compounds extracted from both the roots and aboveground parts of Limonium gmelini. Several methods of extraction, including ultrasound-assisted extraction (UAE), conventional maceration (CM), and supercritical fluid extraction (SFE), were employed to obtain bioactive fractions. Chemical profiling, primarily represented by monosaccharides and polyphenolic compounds, was characterized and analyzed using proton nuclear magnetic resonance spectroscopy (1H-NMR) and gas chromatography-mass spectrometry (GC-MS) techniques. While polyphenol-rich fractions exhibited significant antibacterial activity, particularly against Staphylococcus epidermidis, polysaccharide-rich aqueous fractions showed minimal antibacterial activity. Among the methods, CM and UAE yielded higher polyphenol content, whereas SFE provided more selective extractions. Notably, methanolic SPE fractions derived from the roots were especially enriched in active polyphenols such as gallic acid, myricetin, and naringenin, and they exhibited the highest antibacterial activity against Staphylococcus epidermidis. In contrast, extracts from the aboveground parts showed more moderate activity and a partially different chemical profile. These findings underscore the importance of plant part selection and support the targeted use of root-derived polyphenol-enriched fractions from L. gmelini as promising candidates for the development of natural antibacterial agents. Further investigation is needed to isolate and validate the most active constituents for potential therapeutic applications.